Estudio preliminar de paleofloras cretácicas procedentes de la base de la Formación Loncoche (Mendoz - Álvarez-ramis, Concepción; Prámparo, Mercedes; Papú, Oscar (Coloquios de Paleontología, 2004)
A paleobotanical study is presented, which was carried out on the Cretaceous beds from Calmu-Co and Ranquil-Co (Mendoza, Argentina). This study was aimed to the determination of its diversity, ecological and environmental characteristics in order to establish later correlations with those found in the Spanish Cretaceous beds from Sierra de Guadarrama (Madrid, Spain).The aim of this article focuses on identifying the principal groups of plants in accord with anatomical and morphological characteristics and the presence of its pollen, fruits, seeds etc. In this research we have estimated the fossil plants remains of doubtful classification amounted up lo 80%. These rests determined at the family, genus, etc. level represented the remainder 20% of the total. Based on the differences between the paleomacroflora and the palynomorphs a series of paleoenvironmental remarks are proposed.